2005
DOI: 10.1183/09031936.05.00002105
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clearance from small airways decreases with age

Abstract: The prevalence of respiratory symptoms increases with age. Age has been found to be negatively associated with large airway clearance. The small airways region is considered important for development of airway disease.Clearance after the first 24 h was studied in 46 healthy subjects with a wide age distribution, (mean 42, range 19–81 yrs). All subjects inhaled monodisperse 6 μm Teflon particles labelled with111In, with an extremely slow inhalation flow (0.05 L·s−1). The particles were mainly deposited in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
88
2
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(100 citation statements)
references
References 31 publications
5
88
2
5
Order By: Relevance
“…The positive rate of H. influenzae detection was higher among the older patients, probably reflecting impaired mucociliary clearance and underlying chronic respiratory illness among them (21,22). H. influenzae is commonly involved in acute exacerbation of chronic bronchitis and chronic obstructive pulmonary disease (23).…”
Section: Discussionmentioning
confidence: 99%
“…The positive rate of H. influenzae detection was higher among the older patients, probably reflecting impaired mucociliary clearance and underlying chronic respiratory illness among them (21,22). H. influenzae is commonly involved in acute exacerbation of chronic bronchitis and chronic obstructive pulmonary disease (23).…”
Section: Discussionmentioning
confidence: 99%
“…However, there hypotheses for the cause of air trapping in lungs of elderly people. Progressive decline in respiratory and cardiac function causes alteration of alveolar dead space and shunts, possibly contributing to air trapping [4].…”
Section: Discussionmentioning
confidence: 99%
“…Air trapping is a term to describe retention of gas in all or part of a lung in the expiratory phase [4]. In one CT study, it was defined as an approximately 111.9 ± 46.3 (mean ± standard deviation) HU increase in mean lung attenuation in all three levels [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reasonable to assume that this observed susceptibility is due to the effects of lung and cardiovascular diseases in older individuals. Svartengren et al (2005) reported that long-term small bronchial clearance of 6-μm diameter particles was negatively correlated to age in healthy subjects aged 19-81 years. Age is obviously a difficult parameter to incorporate in dosimetric calculations.…”
Section: Respiratory Tract Diseasementioning
confidence: 99%